Kegiatan Belajar Sambil Bermain di Tk Aisyiyah Kampung Sawah, Jakarta Utara - Muhammad Aydin Azmi; Muhamad Yusuf Alfauzi (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
KKN (Community Service Program) is a program organized by the University of Muhammadiyah Jakarta as a form of implementation of al-ma'un theology towards caring and progressive students so that the KKN program can be carried out in accordance with the locations determined by the Institute for Research and Community Service. This learning while playing program was attended by 10 kindergarten students. This number of students is based on the current conditions at TK Aisyiyah 16 Kampung Sawah. This KKN program raises the topic of learning while playing using input and output methods. The program is carried out in a slum environment with a limited number of students where this kindergarten operates and competes with other kindergartens. The purpose of this program is to increase effectiveness and creativity in learning and to increase the attractiveness of early childhood learning. The results of this program can be concluded that during the learning activities, while playing at Kindergarten Aisyiyah 16 Kampung Sawah, North Jakarta, it went well and smoothly, even though there were several obstacles they could still be overcome and the increase in the number of students, from 10 students, increased by 5 people so that it became 15 students and The students were very enthusiastic about the activities carried out.